One Pot Synthesis of Calcium Sulfate Hemihydrate from Fishbone-derived Carbon - Teguh Wirawan; Mukhamad Nurhadi; Agung Rahmadani; Yuniar Ponco Prananto; Zhiying Zhu; Sin Yuan Lai; Hadi Nur (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Calcium Sulfate Hemihydrate (CSH) with uniform morphology and high crystallinity were successfully prepared by a precipitation-hydrolysis method in a concentrated sulfuric acid solution containing fishbone-derived carbon. The CSH was produced by carbonization of fishbone powder at 500 °C for 2 h, followed by sulfonation with concentrated sulfuric acid for 3 h. The solid mixture was washed until the pH of 2, then left at room temperature for 3 days. Physical properties of synthesized CSH were characterized using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), wavelength dispersive X-ray fluorescence (WDXRF), Scanning Electron Microscope (SEM), nitrogen adsorption-desorption isotherm, and melting point test. It is concluded that the CSH were formed due to hydrolysis of fishbone-derived carbon in a moderately concentrated sulfuric acid solution of carbon-derived fishbone and crystallization into a fibrous octa calcium phosphate (OCP) form. In this research, effect of crystal growth time, effect of pH during the crystal growth, and effect of volume of the solution were also investigated. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).